Realitas Keluarga di Malang Raya dan Pelayanan Pastoral Gereja - Maro, Kornelius (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2016)
Each family is the cell or nucleus for social life of any society. As a cell, the role of each family is very substantial for building up a civilized social structure. The region of Greater Malang, comprising the Malang District and the two cities of Malang and Batu, has to cope with such serius problems regarding family life. The Jawa Pos daily newspaper with its three Radars, namely Radar Malang, Radar Kanjuruhan and Radar Batu, is frequently reporting various and serious problems the families have to handle. This article argues that in such condition, the Catholic Church, particularly the Family Commission of the Malang Diocese is convinced to have a call to present God’s mercy to the people. The writer tries to elabore the ministry of the local Church for families, demonstrating God’s merciful work among the people. Through family ministry, the Church could show God’d face that enlightens the gloomy fate of the people in this region.